Management of Hirayama Disease through Panchakarma- A Case Report - Amrithalatha , K; Jigeesh , P P (International Research Journal of Ayurveda & Yoga, 2023)
Hirayama disease (HD) also called as Monomelic amyotrophy (MMA) is characterized by juvenile onset of unilateral muscular atrophy of a distal upper extremity. The pathogenic mechanism of Hirayama disease is cervical cord compression by the posterior dura with forward displacement in the neck flexed position. Here is a case report of a 26 year old male with HD who had been treated at outpatient and inpatient level of VPSV Ayurveda hospital. The case was considered as a Vatavyadhi and the treatment protocol applied accordingly with incorporation of treatment of Apabahuka particularly. The treatment consisted of a variety of treatments including Udvartana, Snehapana, Swedana, Virechana, Vasthi, Nasya and Rasayana. Even though the condition of the patient was irreversible, the patient could hinder the course of disease during follow up and was able to regain the functional status after restarting the treatment later. The case highlights the improvement in quality of life of Hirayama patient along with improvement in UEFI score after Ayurvedic management.